2022
DOI: 10.1007/s13399-022-03645-0
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective response and chemometric approaches to enhance the phytochemicals and biological activities of beetroot leaves: an unexploited organic waste

Abstract: Research on medicinal plants is developing each day due to inborn phytochemicals, which can encourage the progress of novel drugs. Most plant-based phytochemicals have valuable effects on well-being. Among them, beetroot leaves (BL) are known for their therapeutic properties. Here, three solvents, namely, acetonitrile, ethanol, and water, and their combinations were developed for BL extraction and simultaneous assessment of phytochemical compounds and antioxidant and antifoodborne pathogen bacteria activities.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Then, 10 μL of cell suspension of the studied microorganism was added to a final inoculum concentration of 10 6 colony-forming unit (CFU)/mL and incubated overnight at 37 °C. A volume of 25 µL of thiazolyl blue tetrazolium bromide (MTT) at 0.5 mg/mL was added to the wells and incubated at room temperature for 30 min [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, 10 μL of cell suspension of the studied microorganism was added to a final inoculum concentration of 10 6 colony-forming unit (CFU)/mL and incubated overnight at 37 °C. A volume of 25 µL of thiazolyl blue tetrazolium bromide (MTT) at 0.5 mg/mL was added to the wells and incubated at room temperature for 30 min [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…For each test, the L, E, and C compounds were deposited into the respective well to perform a two-fold serial dilution from the original sample with a final volume of 100 µL per well. Then, 10 µL of cell suspension of the studied microorganism was added to a final inoculum concentration of 10 6 colony-forming unit (CFU)/mL and incubated overnight at 37 • C. A volume of 25 µL of thiazolyl blue tetrazolium bromide (MTT) at 0.5 mg/mL was added to the wells and incubated at room temperature for 30 min [24].…”
Section: Determination Of Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest activity was shown by the distilled water extract of Euphorbia resinifiera (Figure13). 24 Notwithstanding the extraction method, the aqueous-methanol (70%) remains the best solvent for extracting polyphenols and flavonoids. Also,the extracts of this solvent show the best free radical scavenging activity, followed by methanol distilled water.The same observations were reported by Lapornik et al, 20 who showed that the low content of phenolic compounds inaqueous extracts might be due to the absence of oxidases.…”
Section: Total Antioxidant Capacitymentioning
confidence: 99%
“…10 Few studies were found about beet leaves, as a by-product, reporting their bioactive compounds content and therapeutic applications. 37 The ethanolic extract of beet leaves was shown to have anti-quorum-sensing activity using the bio-monitor strain of Chromobacterium violaceum which secretes the violacein pigment. A 50% decrease in violacein production was observed without change in the cell viability confirming its ability to block the cellular interaction and signaling without inhibiting the cell growth.…”
Section: Agro-food Biowaste With Biofilm Inhibitory Effect Onion Peelmentioning
confidence: 99%